The addition of pineapple waste extract in feed on the growth and survival of white shrimp (Litopenaeus vannamei) - Hasibuan, Sakinah; Salamah, Salamah; Mainisa, Mainisa; Hatta, Muhammad; Khalil, Munawwar (Universitas Malikussaleh, 2023)
This study aims to reduce production costs for feed by adding the pineapple waste extract to commercial feed which increases feed utilization efficiency, relative growth rate, protein efficiency ratio, Survival rate, water quality, and Organoleptic Test. This research was conducted from March 31 to April 28, 2022. At the Hatchery and Technology Laboratory Faculty of Agriculture Department of Aquaculture. This study used a non-factorial Completely Randomized Design (CRD) consisting of four treatments and three replications. Treatment A (0% pineapple waste extract + 100 gr feed) B (3% pineapple waste extract + 100 gr feed) C (4% pineapple waste extract + 100 gr feed) D (5% pineapple waste extract + 100 gr feed). The best results from treatment C with feed utilization efficiency of 80.45%, relative growth rate of 4.79%/day and protein efficiency ratio of 1.73%/day. Survival 81,66% and Water Quality. Temperature 26 - 28 oC, DO 7,0 - 7,5 mg/L, pH 7,1 - 7,3, Salinity 32 ppt, Ammonia 0,04-0,08 mg/L. and Organoleptic Test of Color and Scent, the best feed has a very brown color and does not have an overpowering Scent.Keywords: Growth; Pineapple; Survival rate; Vaname Shrimp.